S163. GLUTAMATERGIC METABOLITES IN THE PSYCHOSIS SPECTRUM: FROM HIGH RISK SAMPLES TO FIRST EPISODE PSYCHOSIS. (18th May 2020) - Fortea, Adriana; Masias, Mireia; Pariente, Jose; Ilzarbe, Daniel; Badia, Francina; Valli, Isabel; De la Serna, Elena; Baeza, Inmaculada; Castro-Fornieles, Josefina; Sugranyes, Gisela
Abstract: Background: The N-methyl-D-aspartate receptor hypofunction model of schizophrenia suggests that dysfunction of these receptors leads to an excess release of glutamate and could explain the brain structural abnormalities characterizing these patients. However, glutamatergic pathways underlying transition to psychosis are yet unclear. Methods: Youth with recent onset psychosis (FEP), within the first 5 years of disease, individuals with high risk for psychosis (HR) –including participants with psychosis risk syndrome meeting SIPS/SOPS criteria and offspring of parents with bipolar disorder or schizophrenia –, and healthy volunteers, were recruited and scanned with a 3T Siemens scanner. Magnetic resonance spectroscopy was performed using a 2x2x2 cm3 voxel (VOI) placed in the middle frontal region. Ratios of glutamate (Glu), and glutamate + glutamine (Glx) were quantified using LCModel. Results: 18 adolescents with FEP, 33 HR and 32 healthy controls (HC) were included in the analysis. There were no significant differences between groups in mean age (16.4±2.1 vs 15.7±2.7 vs 16.8±1.9; F=2.0, p=.139), but there were trend-level differences in gender (%females: 33.3% vs 57.6% vs 68.8%; Х2=5.9, p=.052). Multivariate models controlling for gender showed a trend-level effect of group in Glu (F=2.9, p=.062), but not in Glx. Post-hoc pairwise contrasts for Glu revealed significantly higher Glu levels in HR individuals (1.38±0.16) compared to FEP (1.27±0.20) and HC (1.31±0.15). Discussion: Our findings support that increased Glu in the prefrontal cortex may index risk of psychosis from the early stages of the disease, during adolescence. Our observations suggest a possible hyperglutamatergia in premorbid stages that may normalize –or even decrease – after illness onset, possibly related to treatment or compensatory mechanisms. While requiring replication in a larger sample and including follow-up through transition in HR individuals, our findings raise the possibility that abnormal glutamatergic metabolism in the prefrontal cortex could be used as a potential biomarker of illness and putative treatment target.